Parametric optimization of Edm on Hastelloy C-276 Using Taguchi L18 Technique - Khadar Basha, SK; Kolli, Murahari; V.Jagannadha Raju, M (International Journal of Engineering and Technology, 2018)
Due to development in machining science the use of composites and alloys is a great deal for every industry. Hastelloy C276 the most versatile corrosion resistant nickel based super alloy which is used for industrial applications is considered for doing the Â Â Â Â Â Â Â Â Â Â Â experiments .The high nickel and molybdenum content provides better corrosion resistance at extreme environments. In this report, the experiments are performed by using Taguchi L18 technique and their results are used for performance of each process parameters on their output responses. The process parameters considered for experimentation are discharge current, pulse- on- time, type of electrode and pulse off time for the output responses of material removal rate and surface roughness. Eco-friendly (drinking water) is used as a dielectric fluid. The experiments are designed and conducted using Taguchi L18 technique and analyze the influence of each process parameters on machining performance characteristics. Further, mathematical equations were developed using the statistical software MINITAB17.0.ANOVA is used for analyzing the experimental results obtained. It was observed from the response table that the average values of MRR and SR for pulse on time, discharge current, electrode are identified as important process parameters.Â Â